2020
DOI: 10.1186/s13073-020-00734-5
|View full text |Cite
|
Sign up to set email alerts
|

Translating insights from neuropsychiatric genetics and genomics for precision psychiatry

Abstract: The primary aim of precision medicine is to tailor healthcare more closely to the needs of individual patients. This requires progress in two areas: the development of more precise treatments and the ability to identify patients or groups of patients in the clinic for whom such treatments are likely to be the most effective. There is widespread optimism that advances in genomics will facilitate both of these endeavors. It can be argued that of all medical specialties psychiatry has most to gain in these respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 137 publications
1
66
0
Order By: Relevance
“…The ENIGMA consortium performed a meta-analysis of 760 patients with SCZ and 957 healthy participants and revealed that the cognitive function of patients with SCZ is associated with the connectivity of the overall brain structure ( 46 ). Another study indicated that antipsychotic drugs resulted in an acute extrapyramidal response in the body by acting on two single nucleotide polymorphisms (SNPs; rs938112 and rs2987902) of two genes (LSMAP and ABL1) and destroying the binding sites of key transcription factors ( 47 ), LSAMP is an adhesion molecule of neuronal cells that participates in Neurogenesis, neurite outgrowth and plasticity ( 48 ), Abelson non-receptor tyrosine kinase (ABL1) is related to neurodegenerative diseases such as Parkinson's disease ( 48 ); the schizophrenia genomics platform is able to further elucidate the pathogenesis of SCZ ( 49 ) and provide therapeutic prospects for personalized therapy ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ENIGMA consortium performed a meta-analysis of 760 patients with SCZ and 957 healthy participants and revealed that the cognitive function of patients with SCZ is associated with the connectivity of the overall brain structure ( 46 ). Another study indicated that antipsychotic drugs resulted in an acute extrapyramidal response in the body by acting on two single nucleotide polymorphisms (SNPs; rs938112 and rs2987902) of two genes (LSMAP and ABL1) and destroying the binding sites of key transcription factors ( 47 ), LSAMP is an adhesion molecule of neuronal cells that participates in Neurogenesis, neurite outgrowth and plasticity ( 48 ), Abelson non-receptor tyrosine kinase (ABL1) is related to neurodegenerative diseases such as Parkinson's disease ( 48 ); the schizophrenia genomics platform is able to further elucidate the pathogenesis of SCZ ( 49 ) and provide therapeutic prospects for personalized therapy ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this initiative was to bring medicine into a new era, by changing how medicine has been traditionally conceptualized and applied in all clinical areas [2]. The goal of 'precision medicine' is to treat patients based on their individual characteristics, including clinical presentation and / or biological markers and to understand which prevention strategies for a particular disease would work better in specific groups of people [3]. This approach is in contrast to a one-size-fits-all approach, in which disease treatments and prevention strategies are developed for the average person, without considering the possible differences between subjects.…”
Section: Zusammenfassungmentioning
confidence: 99%
“…For instance, the eicosanoids, a family of metabolites derived from oxygenated polyunsaturated fatty acids, have been found to play an important role in inflammatory mechanisms and possibly in psychiatric disorders [19,20], thus highlighting the important role of the inflammation pathways in the search of biomarkers for psychiatric disorders [19,20]. In addition, the advent of pharmacogenomics, the study of how genes influence an individual's response to drug treatment, has led to the development of assays, that provide clinicians valid information to decide the treatment, basing on the patient's unique genome [3]. For instance, a pharmacogenomics clinical study in patients with moderate-to very severe depression showed that psychiatrists who used the GeneSight genetic test in the selection of an antidepressant obtained significantly higher rates of response and remission, as well as better overall symptom relief [24].…”
Section: Zusammenfassungmentioning
confidence: 99%
“…These comparisons give way to the assumption that linear frameworks will undoubtedly work, albeit in the future. Notably, several researchers have taken care to acknowledge that it will take more time to translate psychiatric genetic information to patient care due to the non-Mendelian nature and heterogeneity of such disorders [102-112]. There has also been a recent increase in the discussion of pharmacogenetic treatment for psychiatric disorders, specifically, examining metabolism rates of currently approved psychiatric medications, response to treatment, gene-drug interactions, or other genetic biomarker differences among individuals [94, 113, 114], or reviewing the literature on such treatments [82, 110, 115-118].…”
Section: Part 1: Emphasizing Linear Translational Frameworkmentioning
confidence: 99%
“…Such research often discusses molecular genomics in a broad context with few or no specific examples of copy number variants, genome-wide association findings, or polygenic risk scores [45, 54, 55, 59, 72, 90, 100, 103, 108-111, 116, 119, 123-125, 128, 129, 150-153], but there is a recent trend of reviewing specific biomarkers and potentially actionable molecular variants (e.g., for gene-drug interactions) in-depth [53, 56-58, 61, 82, 83, 112, 114, 115, 117, 118, 121, 122, 131, 144, 154]. For example, Bousman, et al [115] provided a review of the gene-drug interactions of 91 psychotropic drugs and 16 genetic variants across 5 genes, giving rationale for listing those 16 variants as the minimum panel for pharmacogenetics testing.…”
Section: Part 2: Relying On Molecular Genomic Informationmentioning
confidence: 99%